Maxims and Mountaineers - Adelberger, Jörg (AAeO - Afrikanistik-Aegyptologie-Online, 2009)
Stretching along the upper Benue valley, the area of the Muri Mountains is inhabited by various small ethnic groups whose languages belong to the Chadic language family and two branches of the Niger-Congo language family, namely Adamawa and Benue-Congo. Until the beginning of the 20th century the settlements of these groups were situated on the mountain slopes and hilltops. The rugged and mountainous character of the landscape and the (in pre-colonial times much denser) vegetation cover of the surrounding plains were used as a strategic advantage for defence against enemies. Although various raids were undertaken by the adjacent emirates in the 19th century, the groups of the Muri Mountains were never conquered. With the beginning of British colonial administration, various expeditions and patrols were sent into the area and local groups had to succumb to superior military technology. These patrols visited different parts of the area and were undertaken successively over several years. There is evidence that some of these expeditions would have ended less disastrously for the local groups had they not been intentionally misguided by local factional interests.